Single-frequency upconverted laser generation by phase summation. (22nd March 2023) - Zeng, Xin; Cui, Shuzhen; Jiang, Huawei; Ruan, Bowen; Cheng, Xin; Zhou, Jiaqi; Lin, Zhiquan; Yang, Xuezong; Chen, Weibiao; Feng, Yan
Abstract: The phase summation effect in sum-frequency mixing process is utilized to avoid a nonlinearity obstacle in the power scaling of single-frequency visible or ultraviolet lasers. Two single-frequency fundamental lasers are spectrally broadened by phase modulation to suppress stimulated Brillouin scattering in fiber amplifier and achieve higher power. After sum-frequency mixing in a nonlinear optical crystal, the upconverted laser returns to single frequency due to phase summation, when the phase modulations on two fundamental lasers have a similar amplitude but opposite sign. The method was experimentally proved in a Raman fiber amplifier-based laser system, which generated a power-scalable sideband-free single-frequency 590 nm laser. The proposal manifests the importance of phase operation in wave-mixing processes for precision laser technology.